Clinical Characteristics and Predictors of Outcome for Onconeural Antibody-Associated Disorders: A Retrospective Analysis - Liao, Shaohua; Qian, Ying; Hu, Huaiqiang; Niu, Bing; Guo, Hongwei; Wang, Xiaoling; Miao, Shuai; Li, Chuanfen; Cao, Bingzhen (Frontiers in Neurology, 2017)
Objective: To describe and analyze the clinical characteristics, laboratory data, management and outcome of patients with onconeural antibody associated disorders (OAAD) and identify predictors for poor outcome. Methods: This was a retrospective review of all patients with potential OAAD, who were hospitalized in Jinan General Hospital between September 2009 and July 2017. We clarified the diagnosis, collected comprehensive information and categorized patients into 3 groups: paraneoplastic neurological disorders (PNDs), autoimmune encephalitis (AE) and possible OAAD. Within the 3 groups, we analyzed a range of clinical and laboratory parameters and used univariate and multivariate regression analysis to identify predictors for poor outcome (mRS = 3-6). Results: From 158 patients, we identified 70 who fulfilled the criteria for OAAD, including 44 men (62.9%) and 26 women (37.1%). There were 38 patients (54.3%) in the PNDs group, 14 patients (20%) in the AE group and 18 patients (25.7%) in the possible OAAD group. After the last follow-up, 14 (36.8%), 9 (64.2%), and 12 (66.7%) had a good outcome (mRS = 0-2). However, 6 (15.8%), 2 (14.3%), and 3 (16.7%) died, respectively. Univariate analysis showed that duration prior to the hospital (p = 0.0224) and urinary incontinence/retention (p=0.0043) were associated with poor outcome (mRS = 3-6). After multivariate regression analysis, urinary incontinence/retention (p=0.0388) and an immunocompromised state (p=0.0247) remained as significant factors for poor outcome. Conclusions: Urinary incontinence/retention and an immunocompromised state represent significant predictors of a worse prognosis for patients with OAAD. In contrast, cerebrospinal fluid (CSF) analysis showed that serum autoantibodies and tumor markers, the function of crucial organs, electrophysiology and radiological findings were not associated with a poor outcome.